Sexual Harassment of Women in Selected Local Airlines in Lagos, Nigeria: An Analysis of the ILO Sexual Harassment Indicators - Enaikele, M. D.; Adeleke, A. T.; Adeoye, R. A. (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020DO - 10.58709/kiujhu.v5i1.801.257-265, 2020)
Sexual harassment at the workplace is one of the most frequent and pervasive forms of violence against women. The study explores the prevalence of the ILO sexual harassment indicators; determine the extent of reported cases of sexual harassment by victims to the management of their organizations; and examines the common challenges with the Nigeria statutory labour laws on sexual harassment.  The study focused on female employees of twelve (12) airlines in Lagos, who were randomly selected and sampled with open and close-ended questionnaire. One hundred and nine (109) questionnaires properly filled were analysed. An in-depth unstructured interview was also conducted with five other female employees in each of these airlines. The results show a significant prevalence of multiple forms of sexual harassment among the respondents. There is no provision in the Nigeria Labour Law that specifically addresses sexual harassment at the workplace. Following this, the study recommends that employees who have been harassed should avoid the culture of keeping silent or playing along. Employers of labour should also keep a zero tolerance policy for sexual harassment at the workplace. Government should equally enact stringent labour laws to prevent sexual harassment. Civil Society Organisations should embark on advocacy and sensitization of the public on the effect of sexual harassment of women in workplace. Keywords: Sexual Harassment, Women, Local Airlines, Analysis, ILO Sexual Harassment Indicators.